Visual Abstracts in Medical Journals (Nepalese Medical Journal, 2019)
Social media, especially Twitter, crept into academic fields and have become a vital part of all the medical fields and journals.1 Medical journals have been increasingly using Twitter to disseminate their contents to attract a wider readership. The Transplantation Journal, that started tweeting from 2015 to “improve engagement with readership and connect with the authors”, showed that the papers that were tweeted were three times more likely to be downloaded than the non-tweeted ones (p